Review article: uric acid homeostasis and disturbances - Karwur, Ferry Fredy; Pujiastuti, Dwi Rahayu (Folia Medica Indonesiana, 2017)
This review examined the homeostasis of uric acid in human body and analyzed recent studies of the affecting major variables. Normal uric acid concentration in male is 3.5-7.2 mg/dL and in female is 2.6-6 mg/dL. Daily turnover of normal uric acid ranges from 498-1392 mg/day, miscible pool is 767-1650 mg, reabsorption is 8064 mg/day, renal excretion is 262-620 mg/day and intestine 186-313 mg/day. The dynamics of uric acid is influenced by factors of food, drink, age, history of disease, and genetic. High purine dietary consumption increases blood uric acid by 1-2 mg/dL, 213-290 g/day fructose drinks increases 0.52-1.7 mg/dL, 1.5 g/kgBW sucrose increases 0.61 mg/dL, and 10-20 ml/kgBW beer increases 0.50-0.92 mg/dL. The ABCG2 gene plays a role in bringing uric acid out of the body by 114.31-162.73 mg/dL, SLC2A9 of 5.43-20.17 mg/dL, and SLC22A12 of 5.77-6.71 mg/dL. The data described the homeostasis of uric acid and the magnitude of the impact of environmental (consumption of food, beverages, and lifestyle) and genetic factors. Understanding uric acid homeostasis and its disturbances is important in managing diseases as a consequence of hyperuricemia and hypouryscemia